Solve for z -4(z+1)+7z=8

Math
-4(z+1)+7z=8
Simplify -4(z+1)+7z.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-4z-4⋅1+7z=8
Multiply -4 by 1.
-4z-4+7z=8
-4z-4+7z=8
Add -4z and 7z.
3z-4=8
3z-4=8
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
3z=8+4
Add 8 and 4.
3z=12
3z=12
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3z=12 by 3.
3z3=123
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3z3=123
Divide z by 1.
z=123
z=123
Divide 12 by 3.
z=4
z=4
Solve for z -4(z+1)+7z=8

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top